2021
DOI: 10.1111/famp.12649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 Pandemic on Parent, Child, and Family Functioning

Abstract: To quantify the impact of the COVID‐19 pandemic and public health interventions on parent and child mental health and family relationships, we examined change in individual and family functioning in a sample of parents enrolled in a prevention trial; we examined change before the pandemic (2017–2019) when children were an average of 7 years old to the first months after the imposition of widespread public health interventions in the United States (2020) with paired t tests and HLM models. We examined moderatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
249
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(308 citation statements)
references
References 52 publications
22
249
4
5
Order By: Relevance
“…Regarding children's mental health, 14% of parents in a June 2020 US national survey reported that their children's mental health had worsened during the pandemic (Patrick et al, 2020). Recent longitudinal data indicated large effect sizes regarding increases in children's externalizing (d = 1.59) and internalizing (d = 1.31) problems (Feinberg et al, 2021). Thus, a critical next step is to identify key pathways of risk that can guide interventionists seeking to minimize the immediate impact and forestall a long-term increase in children's mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding children's mental health, 14% of parents in a June 2020 US national survey reported that their children's mental health had worsened during the pandemic (Patrick et al, 2020). Recent longitudinal data indicated large effect sizes regarding increases in children's externalizing (d = 1.59) and internalizing (d = 1.31) problems (Feinberg et al, 2021). Thus, a critical next step is to identify key pathways of risk that can guide interventionists seeking to minimize the immediate impact and forestall a long-term increase in children's mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…This gap between the demand for mental health services and supply, which has existed long before the COVID-19 pandemic, poses a significant threat to the mental resiliency of our children and adolescents [ 4 ]. The COVID-19 pandemic has taken a dramatic toll across the globe and challenged families in unprecedented ways [ 5 ]. One study in the United States found that one in four parents reported that they were experiencing mental health deterioration and one in seven reported that their children’s behavioral health had worsened as a result of food insecurity in the home, loss of childcare services, and disruption in healthcare services [ 6 ].…”
mentioning
confidence: 99%
“…In particular, increase in parent depression and children’s internalizing and externalizing problems from before the pandemic were significant findings, which normally are infrequently observed in developmental and family studies 21 , 22 . During the pandemic, these 2 factors increased 2-fold and were more likely to score in the clinical range 21 .…”
Section: Effects Of Covid-19 Pandemic On Family Functioningmentioning
confidence: 88%
“…Understanding the influence of the pandemic on family functioning is therefore essential in order to plan effective support interventions and preventive measures, and to allocate adequate resources to properly assist families during and after the pandemic. Recent studies in Europe and the US have provided evidence for a significant increase in overall mental distress in people tested before and during the pandemic 20 , and showed a consistent deterioration in parent and child mental and behavioral health during the first months of the pandemic 21 , 22 . In particular, increase in parent depression and children’s internalizing and externalizing problems from before the pandemic were significant findings, which normally are infrequently observed in developmental and family studies 21 , 22 .…”
Section: Effects Of Covid-19 Pandemic On Family Functioningmentioning
confidence: 99%
See 1 more Smart Citation